Differentiated strategies of animal-derived and plant-derived biochar to reduce nitrogen loss during paper mill sludge composting. (September 2022) - Liu, Xiaoming; Wang, Yueqiang; Zhou, Shaoqi; Cui, Peng; Wang, Weiwu; Huang, Wenfeng; Yu, Zhen; Zhou, Shungui
Graphical abstract: Highlights: Animal-derived biochar enhanced the synthesis of acid-insoluble nitrogen (AIN). Plant-derived biochar promoted the accumulation of bioavailable organic N (BON). Animal-derived and plant-derived biochar reduced N loss by 24.40% and 35.50%. Two biochars have different effects on bacterial community and metabolism. Both AIN formation and BON retention were effective strategies for reducing N loss. Abstract: This work aimed to reveal the differences of nitrogen (N) transformation between animal-derived and plant-derived biochar during paper mill sludge composting. Three treatments were established, including CK (no biochar), ABC (animal-derived biochar), and PBC (plant-derived biochar). Results showed that N loss was reduced by 24.43% and 35.50% in ABC and PBC, respectively, compared with CK. Moreover, the contents of acid-insoluble N (AIN) in ABC and bioavailable organic N (BON) in PBC were 6.180 g/kg and 9.269 g/kg higher than in CK (2.602 g/kg and 8.988 g/kg). The protease activity and bacterial abundance associated with the generation of humic N-containing precursors increased in ABC. Low urease activity and a more complex bacterial N-cycling network were found in PBC. Structural equation model confirmed that AIN formation and BON retention were the dominant strategies for animal-derived and plant-derived biochar, respectively. The findings provided multiple pathways to produce N-enriched compost products.